A comparative study of the antithrombotic effect through activated endothelium of garlic powder and tomato extracts using a rodent model of collagen and epinephrine induced thrombosis - Kim, Leeseon; Lim, Yeni; Park, Soo-yeon; Kim, You Jin; Kwon, Oran; Lee, Jin Hee; Shin, Jae-Ho; Yang, Yoon Kyoung; Kim, Ji Yeon (Food science and biotechnology, 2018)
In this study, garlic powder, tomato extract and a mixture of both were analyzed for anti-thrombotic effects using a collagen and epinephrine induced thrombosis model. Rats were randomly assigned to control, thrombosis induced control (COL/EP), garlic powder (G), tomato extract (T) and mixture of garlic powder and tomato extract (GT) groups. Test materials were administered for 7 days and thrombosis was induced by collagen and epinephrine injection. The results showed that G, T, and GT delayed activated partial thromboplastin time and reduced the expression of intracellular adhesion molecule-1 mRNA. Histological analysis of aorta and lung revealed that thrombosis was partially improved by G, T, and GT. Although there was no synergistic effect in GT compared to G and T treatment, this study showed that G, T, and GT have anti-thrombotic effect.